A rare case of polycystic ovarian syndrome, empty sella and pituitary atrophy in a patient with mosaic turner karyotype and mullerian dysgenesis - Shahar, Mohamed Arif; Omar , Ahmad Marzuki; Sukor, Norlela; Abd Wahab, Norasyikin; Zainuddin, Suehazlyn; Mustafa, Norlaila; Kamaruddin, Nor Azmi (Malaysian Endocrine and Metabolic Society, 2013)

(untitled)
An 18-year-old lady presented with primary amenorrheoa and was later confirmed to have mosiac Turner karyotype. The presence of müllerian dysgenesis in the spectrum of uterine agenesis to uterine atrophy has been demonstrated in Turner syndrome (TS) before. Similarly, previous study has described the spectrum of streak ovary to normal and polycystic ovary (PCO) in relation to the X chromosome in TS. We herewith report the first case of mosaic Turner karyotype clustering with empty sella, pituitary atrophy, müllerian dysgenesis and single PCO.